2020
DOI: 10.1177/2048872620919946
|View full text |Cite
|
Sign up to set email alerts
|

Severe obstructive sleep apnea is associated with coronary microvascular dysfunction and obstruction in patients with ST-elevation myocardial infarction

Abstract: Background Coronary microvascular dysfunction and obstruction (CMVO) is a strong predictor of a poor prognosis in patients with ST-segment elevation myocardial infarction (STEMI). Although research has suggested that obstructive sleep apnea (OSA) exacerbates CMVO after primary percutaneous coronary intervention, data supporting a correlation between OSA and CMVO are limited. This study was performed to investigate whether OSA is associated with CMVO, detected as microvascular obstruction on cardiovascular magn… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 27 publications
(39 reference statements)
0
1
0
Order By: Relevance
“…It is associated with an increased risk of cardiovascular comorbidities,1 including hypertension and acute coronary syndrome (ACS). Studies have shown that OSA is linked to a poor prognosis in ACS patients,2 3 raising the question of whether OSA treatment can improve outcomes in this population. Continuous positive airway pressure (CPAP) therapy is the first-line treatment for OSA, yet recent randomised controlled studies have found no benefit from CPAP for secondary cardiovascular prevention 4–6.…”
Section: Introductionmentioning
confidence: 99%
“…It is associated with an increased risk of cardiovascular comorbidities,1 including hypertension and acute coronary syndrome (ACS). Studies have shown that OSA is linked to a poor prognosis in ACS patients,2 3 raising the question of whether OSA treatment can improve outcomes in this population. Continuous positive airway pressure (CPAP) therapy is the first-line treatment for OSA, yet recent randomised controlled studies have found no benefit from CPAP for secondary cardiovascular prevention 4–6.…”
Section: Introductionmentioning
confidence: 99%